Komparasi Bank Syariah di Indonesia dan Malaysia ditinjau dari RBBR dan Islamicity Performance - Yunita Rahmania Herviyani; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
To evaluate Islamic Bank for business continuity is usually measured by the Risk-Based Bank Rating (RBBR), But Islamic Bank as Islamic Business entities also need to be measured in terms of the Islamicity Performance. This study aims to analyze the comparison of Risk-Based bank Rating and Islamicity Performance of 11 Indonesian Islamic Banks and 11 Malaysian Islamic Banks. The Data collection in this research was done by collecting all the annual reports of Banks that has been created as sample over the period 2013-2018. The test result of the independent Samples T-test and Mann-Whitney Test show that there were no differences of Islamic Banks in Indonesia and Malaysia as seen from the aspect of FDR, ROA, CAR, and ZPR. While there were differences of Banks Health level and Islamicity Performance as seen from Earning (ROE) and Zakat Performance (ZPR) aspects.Keywords: Bank Helath Level, Risk-Based Bank Rating, Islamicity Performance, Syariah Banking